Woman’s Struggle to Fight Against Nazi as Reflected in Kristin Hannah’s The Nightingale: A Feminist Approach - Raden Muhammad Ali; Amelya Yunita (Universitas Ahmad Dahlan, 2020)
This article aims to describe the main character’s characterization of the novel The Nightingale by Kristin Hannah and identify the main character's struggle to fight against the Nazi. This research is categorized as library research in which the data are taken from books, journals, and other relevant data. This is also descriptive qualitative research with a feminist approach. The primary data are taken from the novel The Nightingale by Kristin Hannah. The research findings are: First, the novel's main character is Isabelle Rossignol or Juliette Gervaise, or The Nightingale. Her characterizations are (1) rebellious, (2) passionate, (3) brave, etc. Second, the struggle of the main character to fight against Nazi are: (1) joining the France resistance, (2) distributing the terrorist paper, (3) helping the allies to escape from Nazi’s territory, (4) changing her name and starting guerilla across the mount, (5) fighting the Nazi and becoming a political prisoner, (6) trying to survive when the SS agent tortures her in prison.